HAK KESEJAHTERAAN PROGRESIF UNTUK BURUH - Anik Malikah (An-natiq Jurnal Kajian Islam Interdisipliner, 2021)
The development of human rights (HAM) from labor is already experiencing an increase in some aspects, such as wage labor rights, but this improvement or development is still not balanced if associated with rapidly growing labor daily needs, especially the needs of the tree, so labor still get to enjoy the rights and well-being progresifitasnya compared with general operators can get more than enough profit.